Predicting Discharge to Institutional Long‐Term Care After Stroke: A Systematic Review and Metaanalysis. Issue 1 (9th October 2017) - Burton, Jennifer K.; Ferguson, Eilidh E. C.; Barugh, Amanda J.; Walesby, Katherine E.; MacLullich, Alasdair M. J.; Shenkin, Susan D.; Quinn, Terry J.
Abstract : Background/Objectives: Stroke is a leading cause of disability worldwide, and a significant proportion of stroke survivors require long‐term institutional care. Understanding who cannot be discharged home is important for health and social care planning. Our aim was to establish predictive factors for discharge to institutional care after hospitalization for stroke. Design: We registered and conducted a systematic review and meta‐analysis (PROSPERO: CRD42015023497) of observational studies. We searched MEDLINE, EMBASE, and CINAHL Plus to February 2017. Quantitative synthesis was performed where data allowed. Setting: Acute and rehabilitation hospitals. Participants: Adults hospitalized for stroke who were newly admitted directly to long‐term institutional care at the time of hospital discharge. Measurements: Factors associated with new institutionalization. Results: From 10, 420 records, we included 18 studies (n = 32, 139 participants). The studies were heterogeneous and conducted in Europe, North America, and East Asia. Eight studies were at high risk of selection bias. The proportion of those surviving to discharge who were newly discharged to long‐term care varied from 7% to 39% (median 17%, interquartile range 12%), and the model of care received in the long‐term care setting was not defined. Older age and greater stroke severity had a consistently positive association with the need for long‐term care admission. Individuals who had a severe stroke were 26 times as likely to be admitted to long‐term care than those who had a minor stroke. Individuals aged 65 and older had a risk of stroke that was three times as great as that of younger individuals. Potentially modifiable factors were rarely examined. Conclusion: Age and stroke severity are important predictors of institutional long‐term care admission directly from the hospital after an acute stroke. Potentially modifiable factors should be the target of future research. Stroke outcome studies should report discharge destination, defining the model of care provided in the long‐term care setting.